The impact of obesity on metabolic and cardiovascular health: A morphometric retrospective cohort study: Obesity and cardiovascular risk - Yucel, Nurullah; Duz, Meryem Esma; Aygun, Tayfun; Hekimoglu, Gulam; Huyut, Mustafa Ahmet; Savas, Goktug; Seker, Muzaffer (Journal of Surgery and Medicine, 2024)
Background/Aim: Obesity is recognized as a significant risk factor for various diseases, including cardiovascular disease. The link between obesity and adverse health outcomes, particularly cardiovascular ailments, underscores the need for a comprehensive understanding of the associated metabolic and cardiovascular markers. This study aimed to compare individuals with obesity and those without obesity in terms of markers related to metabolism and cardiovascular health. Methods: 136 participants were enrolled in the analysis, comprising 83 individuals with obesity and 53 individuals without obesity. The participants’ demographic data and biochemical test results were collected, including age, sex, fasting glucose, creatinine, cholesterol, triglyceride, and body mass index (BMI). Measurements were taken for various cardiac markers using echocardiographic images. Morphometric parameters of the heart, such as left ventricular (LV) and right ventricular (RV) end-systolic-and-diastolic diameter, ejection fraction, interventricular septum thickness, aortic ascending diameter, and epicardial fat tissue thickness were assessed. Statistical analyses were employed to identify significant differences. Independent-sample t-tests and Pearson correlation tests were used for comparisons between obese and non-obese individuals. Results: Comparisons between obese and non-obese individuals revealed that individuals with obesity exhibited significantly higher levels of fasting glucose (P=0.021), triglycerides (P=0.014), and epicardial fat tissue thickness (P˂0.001). LV ejection fraction was significantly higher in obese individuals than in non-obese participants (P˂0.001) but remained within the normal range. Sex-associated differences in metabolic variables of obesity and non-obesity revealed that the obese male individuals had higher fasting glucose (P˂0.001) and triglyceride levels (P˂0.001) compared to obese female individuals. Moreover, BMI was positively correlated with epicardial fat tissue thickness (r2=0.29, P˂0.001), and triglyceride level was significantly correlated with fasting glucose level (r2=0.19, P˂0.001). Conclusion: The study design allowed for a comparison between obese and non-obese individuals, providing valuable insights into the differences in these markers based on obesity status. The investigation of individuals with elevated BMI levels highlights significant deviations in crucial indicators compared to those with normal levels. These findings emphasize the urgent need to address obesity as a central contributor to the development of diverse diseases and advocate for proactive strategies aimed at mitigating associated health risks.